THE IMPLEMENTATION OF WORDWALL.NET AS A LEARNING MEDIUM TO IMPROVE VOCABULARY ACHIEVEMENT OF SEVENTH-GRADE STUDENTS AT SMP AL AZHAR 3 BANDAR LAMPUNG - Fayza Rahadina Adriani; Feni Munifatullah; Lilis Sholihah (English Language Education Study Program, 2026)
This research explores the use of Wordwall.net as an instructional tool to enhance the vocabulary proficiency of seventh-grade students at SMP Al Azhar 3 Bandar Lampung. Utilizing a quantitative approach with a one-group pre-test and post-test design, the study involved 30 students from class VII C, chosen through cluster random sampling. The instruments used were vocabulary assessments administered before and after the treatment, targeting content words such as nouns, verbs, adjectives, and adverbs. Results from the paired sample t-test revealed a notable improvement in students' vocabulary scores, with the average score rising from 55.78 on the pre-test to 82.56 on the post-test, reflecting a mean gain of 26.78. The calculated t-value (21.492) exceeded the critical value (2.045), and the significance level (p = 0.000) was well below 0.05. All vocabulary components showed significant gains, with the most substantial improvements observed in adjectives and nouns, increasing by 7.72 and 11.4 points respectively. These results demonstrate that Wordwall.net is an effective platform for enhancing vocabulary skills among junior high school learners.